PERBANDINGAN ANTARA BAHASA RONGGA DI MANGGARAI TIMUR DENGAN BAHASA BAJAWA DI NGADA: TINJAUAN LINGUISTIK KOMPARATIF - Krispianus Lalong; Umi Hartati (Universitas Sarjanawiyata Tamansiswa, 2017)
The purpose of this study was to describe similarities and differences between Rongga language in East Manggarai with Bajawa language in Ngada terms of vocabulary. This research is a qualitative descriptive study. The data in this study in the form vocabulary by Rongga language in East Manggarai and Bajawa language in Ngada based of 200 Swadesh Vocabulary plus 100 Prof. H. Kern vocabulary. Therefore, that used data in this research is the vocabulary in Rongga language and Bajawa language it has relation with thats 300 vocabularies. Source of data in this study is the user of the Rongga language in East Manggarai and Bajawa language in Ngada. Data collection methods used in this study can be replicated with te infoman interview about Rongga language vocabulary and Bajawa vocabulary language. Results of this study can be a sign that based on the 200 Swadesh vocabulary plus 100 vocabularies by Prof Kern, that was find 277 vocabulary (92,3%) it has realisation by the vocabulary. By the 277 vocabulary, was find 116 vocabulary that same between the Rongga Language and Bajawa Language, and was find that different 55 vocabulary between Rongga language and Bajawa language. Finally, can be find the conclusion that is between Rongga language and Ngada language it has the realisation.